THE CONTRIBUTION OF BUDDHIST COUNSELING FOR EMPOWERMENT IN SOCIAL WORK PRACTICE - Khetjoi, Sitthiporn; Thasa, Worachat; Raisa-nguan, Saccarak (Journal of Buddhist Education and Research (JBER), 2023)
The academic article aims to explain about Buddhist ethics in communication and the contribution of Buddhist ethics to improve the social worker’s communication skill. Communication can help individuals and groups to conduct a dialogue with one another effectively. Right speech is the noble way of communication that we maintain and avoid language that could evoke a defensive or aggressive reaction that we take care of four components: observations, feelings, needs, and requests. Different levels of communication that result in dialogue in different walks of social life are the basis of a democratic polity. Communication skill is one of the vital skills for all social workers. One path mentioned in the Eightfold Path is Right Speech or Sammavaca. It is the asset of outward communication or use in the case of addressing someone. The Buddha was aware of the power and function of speech in creating or losing such discursive power.